2022
DOI: 10.3233/bmr-210049
|View full text |Cite
|
Sign up to set email alerts
|

The effect of upper limb lymphedema in posture of patients after breast cancer surgery

Abstract: BACKGROUND: Upper limb lymphedema is one of the complications following breast cancer-related surgery. It is a fact that there are alterations in posture of the trunk following surgery, however, there is not much data on whether upper limb lymphedema has any effect on body posture. OBJECTIVES: The main purpose of the study was to investigate the effect of upper limb lymphedema in the trunk posture and spine mobility of patients following breast cancer surgery. METHODS: Twenty-seven women with lymphedema and 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The combination of surgery, radiation and chemotherapy treatment creates favorable conditions for saving the lives of breast cancer patients and prolonging their postoperative survival. However, the treatment is prone to several complications, such as upper limb lymphedema ( 3 ), upper limb dysfunction ( 4 ), subcutaneous effusion ( 5 ), flap necrosis ( 6 ), cancer-related fatigue ( 7 ), pain syndrome ( 8 ), Toxic side effects during radiotherapy and chemotherapy ( 9 ), anxiety and depression ( 10 ), and sleep disorders ( 11 ). All of these complications can seriously impair the physical, functional, emotional and family/social health of patients, which in turn affects the postoperative recovery process and the quality of postoperative survival.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of surgery, radiation and chemotherapy treatment creates favorable conditions for saving the lives of breast cancer patients and prolonging their postoperative survival. However, the treatment is prone to several complications, such as upper limb lymphedema ( 3 ), upper limb dysfunction ( 4 ), subcutaneous effusion ( 5 ), flap necrosis ( 6 ), cancer-related fatigue ( 7 ), pain syndrome ( 8 ), Toxic side effects during radiotherapy and chemotherapy ( 9 ), anxiety and depression ( 10 ), and sleep disorders ( 11 ). All of these complications can seriously impair the physical, functional, emotional and family/social health of patients, which in turn affects the postoperative recovery process and the quality of postoperative survival.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CMT focuses on the physiological factors of stretching and the direction of pressure applied to the tissue to improve tissue strength and extensibility through the proper recovery of fibroblasts and homeostasis of the cytoskeleton [23,24]. Postoperative adhesions cause anterior translation of the humeral head during forward shoulder flexion [35], and stimulation is transmitted to the long head of the biceps brachii [36]. This joint positioning fault can be explained by adhesion of the posterior capsule of the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…Among the recently discussed breast cancer issues is the postural control assessment in women after mastectomy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A review of the above-mentioned publications indicated that the undertaken research was concerned with the impact of mastectomy on body static conditions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and body posture of women who had received mastectomies [ 7 , 10 , 18 , 19 ,…”
Section: Introductionmentioning
confidence: 99%
“…The results of several scientific reports indicate that mastectomies may cause body posture disorders such as asymmetry in the trunk in the frontal plane [ 18 , 21 , 42 , 43 , 44 , 45 , 46 , 47 ], asymmetry in the shoulder girdle [ 23 , 42 , 43 , 44 , 45 , 46 ], the curvature of the spine [ 18 , 30 , 34 , 48 ], anterior–posterior [ 10 , 19 , 24 , 27 , 41 ] deepening of thoracic kyphosis [ 11 , 23 , 34 , 41 , 47 ], deepening of lumbar lordosis [ 47 ], and pelvic abnormalities [ 10 ]. Researchers are currently trying to answer questions surrounding whether the body postures of women after mastectomy depend on which side of the body was operated on [ 7 , 19 , 20 , 32 , 34 , 47 ], the type of procedure performed [ 20 , 21 , 24 , 34 , 39 ], lymphedema [ 26 , 27 , 31 ], the time elapsed since the procedure [ 21 ], breast reconstruction [ 22 , 25 , 28 , 30 , 33 , 40 ], and type reconstruction [ 25 ] as well as the ...…”
Section: Introductionmentioning
confidence: 99%